HUBUNGAN PELAKSANAAN KOMUNIKASI TERAPEUTIK DENGAN KEPUASAN KLIEN AKAN PELAYANAN KEPERAWATAN DIÂ RUANG RAWAT INAP KELAS 3 SHOFA DAN MARWAHÂ RSI HASANAH Â KOTA MOJOKERTO - Triwibowo, Heri; Hamim, Nur (Jurnal Keperawatan Bina Sehat, 2011)
The application of therapeutic communication could affect the clients health progress. But until now, nurse rarely use therapeutic communication, thus affecting the satisfaction of client who receives nursing services. The research objective is to analyze the relationship between implementation of therapeutic communication with client satisfaction who receives nursing services in 3rdClass Shofa and Marwah Patient Room RSI Hasanah Mojokerto. This research design is analytic correlation with cross sectional approach. The population is all client who were treated in 3rdClass Shofa and Marwah Patient Room RSI Hasanah Mojokerto for about 71 people, with 54 people taken as the sample by using consecutive sampling. Independent variable is implementation of therapeutic communication and dependent variable is client satisfaction who receives nursing services. Datas are collected by using questionaire. Then analyzed using the Spearman Rho Test with SPSS version 17.0. Results showed most respondents consider therapeutic communication has been implemented and mostly dissatisfied. There is no relationship between the implementation of therapeutic communication with client satisfaction who receives nursing services at p (0.216) > α (0.05). It means there are two possible causes. First, respondents had less courageous to admit that nurse therapeutic communication has not implemented yet. Second, client satisfaction was affected by other factors outside therapeutic communication. Other possible factors include product quality, price, service quality but in terms of systems and technology, emotional factors, ease, and also management. Nurses should implement their skill on therapeutic communication. The management of this hospital should be aware that his policy must be pleasant to get client’s satisfaction.Keywords: therapeutic communication, client satisfaction, nursing services